Implementation Of Independent Curriculum Toward Quality Early Child Education - Erna Sutamini; Rahmat Mulyono (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
The problem of improving the quality of PAUD institutions' services is almost evenly distributed in all PAUD institutions. One of the causes of this problem is the mindset of the implementers of the PAUD program who still view that quality PAUD is one that physically has complete buildings and facilities. This is supported by facts or testimonies from the public who see infrastructure as an important thing in determining the quality of an institution. The implementation of the independent curriculum as one of the embodiments of the new learning paradigm applied in the Mobilizing School Program (PSP) is very effective as a solution for PAUD institutions to achieve quality PAUD.